Variation on the terpene profile of Ocimum basilicum leaf tea caused by leaves storage conditions and preparation methods (Research, Society and Development, 2022)
The use of teas made by medicinal plants is a consolidated practice in Brazil. The chemical profile of teas can be affected by the storage and handling conditions of the plant material. These conditions can cause volatilization, enzymatic degradation, hydrolysis and oxidation of the secondary metabolites, which can affect the biological properties of the teas. This paper describes how the chemical profile of basil extracts, prepared by aqueous infusion, is affected by variations on the contact time between plant material and boiling water (5, 10 20 and 30 minutes), and the use of whole and fragmented fresh leaves, that were stored according to the methods commonly used by the population: cooling and freezing (7 days). The chemical profile of the extracts was evaluated by GC-MS. The tea in which the highest number of metabolites was extracted, 15 in total.  was obtained using fresh fragmented leaves with 20 minutes of infusion. In the teas prepared by using whole fresh leaves (infusion by 5 to 30 minutes) and frozen leaves (infusion by 30 minutes), 11 metabolites were observed. The teas prepared by using cooled leaves (infusion by 5 to 30 min) and dried leaves (infusion by 30 min) presented 5 metabolites each. In the tea prepared by using dried leaves, with infusion time of 5 minutes, only 2 metabolites were observed. The results indicate that the presence of pharmacological bioactive metabolites in homemade basil’s tea may vary according to the form of storage of the leaves and preparation methods of the tea.